2021
DOI: 10.3390/cells10102632
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic DNA Modifications Upregulate SPRY2 in Human Colorectal Cancers

Abstract: Conventional wisdom is that Sprouty2 (SPRY2), a suppressor of Receptor Tyrosine Kinase (RTK) signaling, functions as a tumor suppressor and is downregulated in many solid tumors. We reported, for the first time, that increased expression of SPRY2 augments cancer phenotype and Epithelial-Mesenchymal-Transition (EMT) in colorectal cancer (CRC). In this report, we assessed epigenetic DNA modifications that regulate SPRY2 expression in CRC. A total of 4 loci within SPRY2 were evaluated for 5mC using Combined Bisul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…The upregulation of IL-1 has been shown in other cancers, including breast, colon, head and neck, lung, pancreas, and melanomas, with patients with high levels of IL-1 having generally poor prognosis [ 25 ]. The downregulation of SPRY2 has been shown in chronic lymphocytic leukemia, non-small cell lung cancer, hepatocellular carcinoma, breast cancer, and prostate cancers [ 26 ], highlighting its tumor suppressor function.…”
Section: Discussionmentioning
confidence: 99%
“…The upregulation of IL-1 has been shown in other cancers, including breast, colon, head and neck, lung, pancreas, and melanomas, with patients with high levels of IL-1 having generally poor prognosis [ 25 ]. The downregulation of SPRY2 has been shown in chronic lymphocytic leukemia, non-small cell lung cancer, hepatocellular carcinoma, breast cancer, and prostate cancers [ 26 ], highlighting its tumor suppressor function.…”
Section: Discussionmentioning
confidence: 99%
“…This disparity in methylation and gene expression levels between primary cancer cells and cell lines seems counterintuitive. Our past studies have made examples out of this phenomenon for genes CXCR4 and SPRY2 in CRC [ 42 , 43 ]. Both of these genes greatly differ in methylation and expression between various CRC cell lines, whereas promoter hypomethylation and increased gene expression was consistently observed in patient tumor samples.…”
Section: Discussionmentioning
confidence: 99%
“…Both of these genes greatly differ in methylation and expression between various CRC cell lines, whereas promoter hypomethylation and increased gene expression was consistently observed in patient tumor samples. For example, among the Sprouty genes aberrantly expressed in CRC, we have previously shown that SPRY2 is also methylated and downregulated in several CRC cell lines [ 43 ]. However, in human CRC samples, we have shown that both the Sprouty genes (SPRY2 and SPRY4) are hypomethylated in the distal promoter regions and upregulated.…”
Section: Discussionmentioning
confidence: 99%
“…11 However, high expression of SPRY2 protein was reported to be associated with poor survival in CRC patients. 12,14,15 SPRY2 was demonstrated to enhance CRC invasion in vitro, 12,16 and is upregulated in the invasive front of primary CRCs. 17 Recently, SPRY2 was also shown to promote epithelial-to-mesenchymal transition of CRC cells through ZEB1 induction and miR-194-5p inhibition, [16][17][18] and enhance the transformed phenotype mediated in part by c-Met upregulation.…”
Section: Introductionmentioning
confidence: 96%